Az Endorois ügy, egy hosszú út eredménye – avagy az afrikai emberi jogvédelmi mechanizmus joggyakorlata és az őslakos népek jogainak védelme - Marinkás, György (Debreceni Jogi Műhely, 2014)
The aim of the current article is to analyse the protection of indigenous peoples’ rights offered by the African human rights mechanism by introducing the Endorois Welfare Council vs. Kenya case[1] (hereafter: Endorois case). The author briefly introduces the preliminaries of the Endorois case, namely how the African mechanism was established and in doing so, he refers to the achievements of the African Commission on Human and Peoples’ Rights (hereafter: Commission) in the field of protecting the rights of the African indigenous peoples, also touching upon the critiques regarding its functioning. Then he briefly introduces why the Ogoni case[2]can be regarded as a milestone concerning the rights of indigenous peoples on the African Continent. In the second part, the author focuses on the Endorois case and analyses it in detail: he introduces both the matters of fact and the legal issues; furthermore he pays attention to the implementation of the decision. Finally, in the third part of the article, the author draws his conclusions based on the above mentioned and makes his recommendations.The author has the opinion that the African mechanism has followed in the footsteps of the Inter-American System and has interpreted the already existing substantial norms in an evolutiv manner, thus achieving tremendous results in the acknowledgement and protection of indigenous rights. They did so with such success that now the “master” – namely the Inter-American Commission on Human Rights – is quoting the student. It follows from the above mentioned that – according to the firm opinion of the author – the African mechanism worth the attention both present time, both in the future, because new trends regarding indigenous rights could arise from the practice of the African Commission.